2017
DOI: 10.1364/boe.8.003656
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence depth estimation from wide-field optical imaging data for guiding brain tumor resection: a multi-inclusion phantom study

Abstract: Abstract:Studies have shown that fluorescent agents demarcate tumor from surrounding brain tissue and offer intraoperative guidance during resection. However, visualization of fluorescence signal from tumor below the surgical surface or through the appearance of blood in the surgical field is challenging. We have previously described red light imaging techniques for estimating fluorescent depths in turbid media. In this study, we evaluate these methods over a broader range of fluorophore concentrations, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…23 (7) is high, or incident light can easily penetrate tissues and the intensity of excitation light becomes high and results in the emission light becoming easy to detect. In 2017, Wirth et al 28 reported that the depth of fluorescence was estimated under a bulk phantom, having μ 0 s of 1.0 mm −1 and μ a of 0.001 mm −1 . Although the results by Wirth et al suggest that the depth of fluorescence was correctly estimated for shallower inclusions, the error of the predicted depth drastically increased for inclusions at depths greater than δ, even when using a correction based on optical properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 (7) is high, or incident light can easily penetrate tissues and the intensity of excitation light becomes high and results in the emission light becoming easy to detect. In 2017, Wirth et al 28 reported that the depth of fluorescence was estimated under a bulk phantom, having μ 0 s of 1.0 mm −1 and μ a of 0.001 mm −1 . Although the results by Wirth et al suggest that the depth of fluorescence was correctly estimated for shallower inclusions, the error of the predicted depth drastically increased for inclusions at depths greater than δ, even when using a correction based on optical properties.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 The correction of optical properties for the detection of PpIX validated with a phantom was found to be suitable for quantitative fluorescence spectroscopy and imaging. 28,34 If there is a region with high δ in brain Table 2 Comparison of (a) mean absorption coefficients, (b) mean reduced scattering coefficients, and (c) optical penetration depths of meningioma and brain tumor. Differences to the means of two measurements are calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Another area for future work could take into account other excitation wavelengths that are being used [20] for exciting biological fluorophores.…”
Section: Journal Of Spectroscopymentioning
confidence: 99%
“…In the surgical setting, we limited acquisitions to reflectance images at 670 and 710 nm, as the optical properties at these wavelengths are needed to estimate fluorescence at depth. 11,12 Three images with the spatial frequency of 0.10 mm −1 were acquired for profilometry at each wavelength. For acquisition of diffuse reflectance values, R d ðf ¼ 1 mm −1 Þ and R d ðf ¼ 0 mm −1 Þ, three phases of f ¼ 1 mm −1 , one uniform illumination (f ¼ 0 mm −1 ), and one dark image were acquired at each wavelength (totaling 16 image acquisitions, requiring ∼4 s total).…”
Section: In Vivo Human Experimentsmentioning
confidence: 99%
“…9,10 Furthermore, by comparing fluorescence signals measured at two wavelengths within the emission spectra of PpIX, we developed a technique to estimate the depth of the fluorescence emissions as well as to distinguish between multiple inclusions at different depths and locations within the surgical field of view (FOV). 11,12 This technique, however, relies on knowledge of the optical (absorption and transport scattering) properties of the tissue being imaged, and places a premium on having a reliable, accurate, and rapid method to estimate these properties across the neurosurgical FOV.…”
Section: Introductionmentioning
confidence: 99%